VOCATIONAL EDUCATION AND SPECIALIST TRAINING IN AUTONOMOUS REPUBLICS OF THE NORTH CAUCASUS DURING THE PRE-WAR PERIOD (1936 - June, 1941) - Kajmarazov, G S (History, Archeology and Ethnography of the Caucasus, 2016)
The article deals with an underinvestigated and important problem - development of vocational education and specialist training in Dagestan, Kabardino-Balkaria, North Ossetia and Chechen-Ingush republic in the pre-war period in the context of the Second World War, which began in Europe, and the rise of security threat to the Soviet Union. Basing on the reliable source materials, the author of the article characterizes the measures taken by the Soviet state and party leaders and local authorities to strengthen the economy, particularly the industrial power of the country. The author shows that even during these hard years the government continued to increase the efforts to develop culture, general and vocational education.